2021
DOI: 10.1186/s12967-020-02695-0
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome of nasopharyngeal samples from COVID-19 patients and a comparative analysis with other SARS-CoV-2 infection models reveal disparate host responses against SARS-CoV-2

Abstract: Background Although it is becoming evident that individual’s immune system has a decisive influence on SARS-CoV-2 disease progression, pathogenesis is largely unknown. In this study, we aimed to profile the host transcriptome of COVID-19 patients from nasopharyngeal samples along with virus genomic features isolated from respective host, and a comparative analyses of differential host responses in various SARS-CoV-2 infection systems. Results Uniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 97 publications
10
37
0
Order By: Relevance
“…We also profiled the host transcriptional profile of the nasal epithelium in a subset of patients. As recently described (Butler et al, 2021;Islam et al, 2021;Lieberman et al, 2020;Ng et al, 2021), we observed an upregulation of genes associated with innate immune cell activation, antiviral defense, inflammation, and cell death. Furthermore, the upregulation of genes associated with neuronal death and the downregulation of genes influencing epithelial integrity and sensory organ development support a mechanism for infection-induced anosmia and ageusia (de Melo et al, 2021;Melo et al, 2021;Rawson and Huang, 2009).…”
Section: Accesssupporting
confidence: 80%
“…We also profiled the host transcriptional profile of the nasal epithelium in a subset of patients. As recently described (Butler et al, 2021;Islam et al, 2021;Lieberman et al, 2020;Ng et al, 2021), we observed an upregulation of genes associated with innate immune cell activation, antiviral defense, inflammation, and cell death. Furthermore, the upregulation of genes associated with neuronal death and the downregulation of genes influencing epithelial integrity and sensory organ development support a mechanism for infection-induced anosmia and ageusia (de Melo et al, 2021;Melo et al, 2021;Rawson and Huang, 2009).…”
Section: Accesssupporting
confidence: 80%
“…In this study we also profiled the host transcriptional profile of the nasal epithelium in a subset of patients. Our findings highlight an upregulation of genes associated with innate immune cell activation, antiviral defense, and inflammation as recently described (72,73). We also observed a transcriptional signature associated with cell death which has been proposed as a key biosignature of COVID-19 infection (74,75).…”
Section: Discussionsupporting
confidence: 83%
“…Not surprisingly, we saw a marked increase in proteins involved in cytokine signaling in immune system (HSA-1280215) in response to viral protein expression, including CD70, IRF9, and TNFSF9. The most significantly upregulated protein we identified was ITGB3 (logFC = +3.32 to +4.78), which has recently been shown to be upregulated in COVID-19 patient lung samples and has been hypothesized to be an alternative receptor for the SARS-CoV-2 virus [26, 27]. We found this ITGB3 upregulation in cells expressing ORF9c, ORF3a, ORF7b, E-protein, and NSP2.…”
Section: Resultsmentioning
confidence: 63%